Fluconazole Resistance among Oral Candida Isolates from People Living with HIV/AIDS in a Nigerian Tertiary Hospital - Osaigbovo, Iriagbonse; Lofor, Patrick; Oladele, Rita (Journal of fungi (Basel), 2017)
Oropharyngeal candidiasis, a common fungal infection in people living with HIV/AIDS (PLWHA), arises from Candida species colonizing the oral cavity. Fluconazole is the preferred treatment and is often used empirically. Few studies have investigated the prevalence of fluconazole resistance in Nigeria. This study aimed at determining the burden of fluconazole resistance among Candida species in the oral cavities of PLWHA. We sampled the oral cavities of 350 HIV-infected adults and an equal number of HIV-negative controls. Candida isolates were identified using germ tube tests, CHROMagar Candida (CHROMagar, Paris, France), and API Candida yeast identification system (BioMérieux, Marcy-l’Étoile, France). Fluconazole susceptibility was determined using the Clinical and Laboratory Standards Institute disc diffusion method. Data were analysed using SPSS version 21 (IBM, New York, NY, USA). The significance level was set at p ≤ 0.05. The isolation rates for Candida amongst HIV-infected subjects and controls were 20.6% and 3.4%, respectively (p < 0.001). In PLWHA, Candida albicans was most frequently isolated (81.3%) and fluconazole resistance was present in 18 (24%) of the 75 Candida isolates. Resistance to fluconazole was present in half of the non-albicans Candida isolates. Fluconazole resistance is prevalent among oral Candida isolates in PLWHA in the study area with a significantly higher rate among non-albicans Candida spp.